DESIGN AND ANALYSIS OF WATERSHED MANAGEMENT USING HEC-RAS SOFTWARE TOOL (International Journal of Engineering Management Science, 2024)
Watershed management is critical for ensuring sustainable water resources and reducing the impact of floods and droughts. The Hydrologic Engineering Center's River Analysis System (HEC-RAS) software tool is widely used for watershed management due to its capabilities in hydraulic modeling and floodplain analysis. This paper presents a comprehensive overview of watershed management principles and demonstrates the application of the HEC-RAS software tool in analyzing and designing effective watershed management strategies. The paper discusses the key features of HEC-RAS, including its hydraulic modeling capabilities, floodplain mapping, and sediment transport analysis. A case study is presented to illustrate the practical implementation of HEC-RAS in watershed management, highlighting its role in flood risk assessment, stream restoration, and erosion control measures. The paper concludes with recommendations for future research and the adoption of HEC-RAS as a valuable tool in watershed management.
Keywords: Watershed management, HEC-RAS, hydraulic modeling, floodplain analysis, flood risk assessment, stream restoration, erosion control